First report of vancomycin-resistant staphylococci isolated from healthy carriers in Brazil - Palazzo, ICV; Araujo, MLC; Darini, ALC (Amer Soc Microbiology, 2005)
Reduced susceptibility or resistance to vancomycin has been reported among clinical isolates of staphylococci in previous studies. In the present study we report on the isolation of four vancomycin-resistant staphylococcal strains from healthy carriers inside and outside the hospital environment. These carriers did not receive treatment with any antibiotic. All coagulase-negative staphylococcal strains showed variable levels of resistance to several antimicrobial agents, including oxacillin, and unstable resistance to vancomycin, with decreased vancomycin MICs (<4 mg/liter) after 10 days of passage in a nonselective medium. However, exposure of these revertants to vancomycin selected staphylococcal strains resistant to vancomycin at very high frequencies (10(-2) and 10(-3)). The vancomycin resistance in these staphylococcal strains was not mediated by the van gene. The cell wall of the staphylococcal strains studied became thickest after culture in medium containing vancomycin, and the differences in cell wall thickness were statistically significant (P < 0.001). Thus, the thickening of the cell wall in these staphylococcal strains may be an important contributor to vancomycin resistance.